Developing Conceptual Understanding through Diagrams: Year 7 Students' Learning of Balanced and Unbalanced Forces - Tenzin, Sherab (Curtin University, 2024)
This study investigated the challenges and opportunities presented to students while drawing conceptual diagrams, through the lens of social constructivist perspectives. Interpretive analysis of student-generated diagrams and their interactions revealed that Year 7 students’ understanding of the concept of balanced and unbalanced forces improved over time, however, their development differed based on their prior knowledge and involvement in discussions. The findings show that drawing diagrams support activities that enhance students’ conceptual understanding.